(untitled) (Discourse of Law and Administration, 2023)
The aim of the article is to consider the relationship between the rule of law standard and the principles of legislative technique in creating tax law. It was indicated that the principles of legislative technique constitute the specification of law-making standards specified in the clause of a democratic state ruled by law. The principles resulting from the rule of law were discussed, and then they were related to selected principles of legislative technique and confronted with the matter of excise tax. It was also considered whether the violation of standards of legislative technique would be tantamount to violation of the democratic rule of law clause.